An Examination of Negative Correlations Using Pearson Correlation Analysis to Optimize the Diversification of Cryptocurrency Portfolios - Widodo, Edi Widodo,; Rahmawati, Eka Putri; Bilqist, Chay Shona (Jurnal Transformatika, 2024)
The purpose of this study is to employ the Pearson correlation approach in order to assess the association between different types of cryptocurrencies. The dataset included in this research comprises daily peak price information for 10 distinct categories of cryptocurrencies with the biggest market capitalizations from October 1, 2017 to December 31, 2022. Assessing and computing the correlation between cryptocurrency pairs with the Pearson correlation coefficient is the objective. The information utilized in this study was acquired from the website www.coinmarketcap.com. Pairs of stablecoins and crypto coin assets have the largest negative correlation, according to the findings of this study, in contrast to pairs of crypto currency assets. The pair ETH-BNB has the strongest positive correlation with a value of 0.948, while the pair LTC-USDT has the most negative correlation at -0.347. In order to replicate the impact of the negative correlation on trading activities, an exchange simulation was performed between the LTC and USDT pairings. Based on the outcomes of the simulation, the asset rise resulting from the exchange of the LTC and USDT pair from January 1, 2022 to December 31, 2022 was 12.09 percent. During the same time period, the asset’s value would have declined by -48.69 percent if LTC was held. Conversely, an expansion of the time period from October 1, 2017 to December 31, 2022 yields an asset gain of 251,047.85 percent as a consequence of the exchange between LTC and USDT. Those individuals interested in reducing risk and diversifying their portfolios with cryptocurrency investments may find this information highly beneficial. The results of this research offer significant contributions to the current body of literature on bitcoin investment and offer investors valuable information